ANALISIS KONSUMSI PANGAN BERBASIS PROTEIN HEWANI DI KABUPATEN LEBONG: PENDEKATAN MODEL AIDS (ALMOST IDEAL DEMAND SYSTEM) - Anggraini, Putry; Priyono, Basuki Sigit; Suryanty, Melly (Jurnal AGRISEP, 2017)
The research to aimed  quantify the level of purchases of cooking oil in households in the city of Bengkulu and to analyze the factors affecting the level of purchases of cooking oil in households in the city of Bengkulu. The research area decided by purposive. The data that use in this research are primary data and secondary data. Analyzed method use Multiple Linear Regresion derived by the square of the least square ordinary (Ordinary Least Square / OLS). The result show : The average purchase of cooking oil in Bengkulu City every month of 6.6 kg / household / month. Household income positive significant effect on the purchase of cooking oil in the city of Bengkulu, and number of branded cooking oil purchases negative significant effect on the purchase of cooking oil in the city of Bengkulu. However, of age, education, household spending, and perceptions of the cooking oil products did not significantly influence the purchase of cooking oil in the city of Bengkulu.Keywords: Purchase, cooking oil, household